A Canvas on which to Feast: A Canadian Adventure. (28th June 2021) - Spiller, Neil
Abstract: Since 2020, AD Editor Neil Spiller has been Azrieli Visiting Critic at Carleton University in Ottawa, Canada. This appointment necessitated a new approach to his teaching, one that is highly direct and fast‐paced. Having run many iterations of academic year‐long studios, he swiftly had to adapt his solo tutoring to short six‐week option studios, which proved to be a reinvigorating experience. Here he shares some of the fruits of his and the students' labour.